Microsphere-Based Scaffolds Carrying Opposing Gradients of Chondroitin Sulfate and Tricalcium Phosphate - Gupta, Vineet; Mohan, Neethu; Berkland, Cory J.; Detamore, Michael S. (Frontiers in Bioengineering and Biotechnology, 2015)
Extracellular matrix (ECM) components such as chondroitin sulfate (CS) and tricalcium phosphate (TCP) serve as raw materials and thus spatial patterning of these raw materials may be leveraged to mimic the smooth transition of physical, chemical and mechanical properties at the bone-cartilage interface. We hypothesized that encapsulation of opposing gradients of these raw materials in high molecular weight poly(D,L-lactic-co-glycolic acid) (PLGA) microsphere-based scaffolds would enhance differentiation of rat bone marrow stromal cells (rBMSCs). The raw material encapsulation altered the microstructure of the microspheres and also influenced the cellular morphology that depended on the type of material encapsulated. Moreover, the mechanical properties of the raw material encapsulating microsphere-based scaffolds initially relied on the composition of the scaffolds and later on were primarily governed by the degradation of the polymer phase and newly synthesized extracellular matrix by the seeded cells. Furthermore, raw materials had a mitogenic effect on the seeded cells and led to increased glycosaminoglycan (GAG), collagen, and calcium content. Interestingly, the initial effects of raw material encapsulation on a per-cell basis might have been overshadowed by medium-regulated environment that appeared to favor osteogenesis. However, it is to be noted that in vivo, differentiation of the cells would be governed by the surrounding native environment. Thus, the results of this study demonstrated the potential of the raw materials in facilitating neo-tissue synthesis in microsphere-based scaffolds and perhaps in combination with bioactive signals, these raw materials may be able to achieve intricate cell differentiation profiles required for regenerating the osteochondral interface.